2014
DOI: 10.3390/biom4010140
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Guanine Oxidation Products in Double-Stranded DNA and Proposed Guanine Oxidation Pathways in Single-Stranded, Double-Stranded or Quadruplex DNA

Abstract: Guanine is the most easily oxidized among the four DNA bases, and some guanine-rich sequences can form quadruplex structures. In a previous study using 6-mer DNA d(TGGGGT), which is the shortest oligomer capable of forming quadruplex structures, we demonstrated that guanine oxidation products of quadruplex DNA differ from those of single-stranded DNA. Therefore, the hotooxidation products of double-stranded DNA (dsDNA) may also differ from that of quadruplex or single-stranded DNA, with the difference likely e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 49 publications
4
35
0
Order By: Relevance
“…This is almost identical to the control spectrum except for the addition of oxygen to the w 5 ion and the lack of the w 4 ion. Furthermore, guanine is the most readily oxidized nucleobase in condensed-phase experiments [73,74], supporting the observations from this gas-phase oxidation experiment. This is the first demonstration of the oxidation of DNA via ion/ion reactions.…”
Section: Resultssupporting
confidence: 76%
“…This is almost identical to the control spectrum except for the addition of oxygen to the w 5 ion and the lack of the w 4 ion. Furthermore, guanine is the most readily oxidized nucleobase in condensed-phase experiments [73,74], supporting the observations from this gas-phase oxidation experiment. This is the first demonstration of the oxidation of DNA via ion/ion reactions.…”
Section: Resultssupporting
confidence: 76%
“…In the first stage of the process an electron from a molecule of guanine is abstracted with the participation of a hydroxyl radical (the abstraction of an electron can also be an effect of quantum radiation or some other equally strong attack, by an oxidant such as a ferrous radical 15 , or as a result of the reaction of type I photosensitizers). [16][17][18][19] In the second stage of the reaction, the final product is formed (Fig. 4).…”
Section: -Hydroxy-2'-deoxyguanosinementioning
confidence: 99%
“…It has been established that guanine is the most effective sink for oxidative damage in DNA (Steenken and Jovanovic 1997; Morikawa et al 2014). As such, we focused on the cleavage probabilities at isolated guanine bases and guanine triplet repeats within two double-stranded sequences of interest, designated single-G and triple-G (Table 1) annealed to their complements, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As free base release analysis, quantification of products like C (8-oxo-G), and the ESR studies of mechanisms of 8-oxo-G cation radical formation from guanine cation radical has pointed to guanine as a sink for DNA damage induced by an oxidative pathway (Shukla et al 2004; Steenken and Jovanovic 1997; Morikawa et al 2014) we analyzed the relative probability of strand break occurrence at a guanine triplet compared to a single guanine base with identical flanking bases. This investigation builds on previous work in which ultraviolet A (UVA, wavelength 400-315 nanometers) irradiation studies identified GGG as a sink for base damage, showing dramatic increases in the production of 8-oxo-G through one-electron oxidation of the G within GGG regions, which resulted in strand breaks after hot piperidine treatment (Chung et al 1992).…”
Section: Discussionmentioning
confidence: 99%